SAW-TOPSIS Implementation To Determine An Appropriate DBMS Software - Anggrainingsih, Rini; Wiyanto, Aditya; Aziz, Abdul (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Selection an appropriate Database Management Software, is a crucial part to ensure operational excellence businesses firm. Database management software used to organize and manage the company’s data so that they can be efficiently accessed and used to improve operational and decision quality. However, a senior manager as decision maker sometimes lacks the comprehensive knowledge to choose a suitable database management software which meets with business needs. Then, The manager determines a database management software based on a consultant or vendor offer. On the other hand, a consultant or vendor has an interest in to sell their product, so they tend to lead manager to choose their product even though it is not fulfilling business needs. We present a decision support application to help the manager to select an appropriate database management software (DBM) for their company, using Simple Additive Weighting (SAW) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. We observe SQL Server, MySQL, Oracle, DB2, and PostgreSQL as five top database management software and investigate the detail about cost, storage capacity, security, supported the operating system and supported programming language as key criteria to select best database management software from their official website. Then, we combining SAW and TOPSIS method to choose the best appropriate DBM software based on user requirement through computation program and validate our application performance includes the user interface, usability and accuracy result to 50 database engineers expert as respondent. The results are as follows; 1) 86 % of respondents are satisfied with application user interface, 2) 94% are happy with application usability and 3) 86% are pleased with the accuracy of the computation. Overall, this study provides a decision support application to determine an appropriate database management software based on business needs by combining SAW and TOPSIS methods.